Neuropsychiatric Symptoms of Alzheimer's Disease and Caregiver Burden - Iravani, Behnam; Abdollahi, Elaheh; Eslamdoust-Siahestalkhi, Fatemeh; Soleimani, Robabeh (Frontiers in Neurology, 2022)
Introduction/Objectives In addition to cognitive decline, one of the most important problems for caregivers of patients with Alzheimer's is neuropsychiatric symptoms (NPS). This study aimed to evaluate the NPS in patients with Alzheimer's disease (AD) and investigate its relationship with caregiver burden (CB). Methods In a cross-sectional study of 85 patients with AD referred to Shafa Hospital in Rasht and their caregivers in 2020, information was collected using a demographic questionnaire, Neuropsychiatric Inventory Questionnaire (NPI-Q), and the Caregiver Burden Inventory (CBI). Data were analyzed by Spearman correlation, t-test, and linear regression, with SPSS version 22. Results The mean age of the patients and their caregivers were 74.95 ± 8.87 years and 43.98 ± 11.38 years, respectively. The mean total score of NPS in patients with AD was 44.25 (0–144) and the mean CB score was 36.27 (0–96), which was a moderate level. According to the results, 91% of patients had apathy, while happiness/euphoria was reported as the most uncommon symptom. In addition, there was a significant relationship between the score of NPS and CB (r = 0.542, P < 0.0001), as well as all its sub-components, time-dependence burden with more correlation (r = 0.509, P < 0.0001), and social burden with less correlation (r = 0.352, P < 0.001). NPS, hallucination, aberrant motor behavior (AMB), delusion, and depression were most correlated with CB. Also, the mean score of CB was significantly higher in women than in men (P = 0.045). Living in a rural area had a significant relationship with NPS score (P = 0.026). Also, linear regression showed that with increasing 1 year of patients' age, the mean score of patient's NPS decreased by 0.374 (P = 0.048). Conclusion Neuropsychiatric symptoms, especially hallucination, aberrant motor behavior (AMB), delusion, and depression were associated with caregiver burden. Apathy was the most common symptom in patients with AD.